2019
DOI: 10.2147/cia.s201777
|View full text |Cite
|
Sign up to set email alerts
|

<p>The correlation of muscle thickness and pennation angle assessed by ultrasound with sarcopenia in elderly Chinese community dwellers</p>

Abstract: Background: Sarcopenia is typically defined as the loss of muscle mass, strength and low physical performance with aging. Ultrasound is a safe and easy method for evaluating muscle mass and quality by muscle thickness (MT) and pennation angle (PA), respectively. Although the positive correlations between MT and muscle mass and handgrip strength were observed, the relationship between MT, PA and physical performance remains unclear. Purpose: This study aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In muscles where the orientation of the fibers is almost parallel to their fascia (e.g., RF), the PA could be difficult to measure and not determinable (76). Its measure can be taken with a US longitudinal scan in the same place of RF thickness parameter, keeping the transducer compression on the skin as low as possible and using a suitable amount of ultrasound gel (Figure 7) (88).…”
Section: Techniquementioning
confidence: 99%
“…In muscles where the orientation of the fibers is almost parallel to their fascia (e.g., RF), the PA could be difficult to measure and not determinable (76). Its measure can be taken with a US longitudinal scan in the same place of RF thickness parameter, keeping the transducer compression on the skin as low as possible and using a suitable amount of ultrasound gel (Figure 7) (88).…”
Section: Techniquementioning
confidence: 99%
“…A systematic review showed that US was a reliable and effective tool to evaluate the muscle size of the elderly and a feasible method to predict lean body weight (59). Muscle thickness, as measured by US, has a good correlation with muscle volume as measured by DXA, which is the gold standard of measurement for muscle volume (60). A study based on US also found that the feather angle of the medial and lateral head of the gastrocnemius was related to lower limb function in women (61).…”
Section: Ultrasound (Us)mentioning
confidence: 99%
“…These parameters may be altered in older subjects, in lower limb antigravity muscles such as quadriceps femoris and gastrocnemius medialis [28]. Therefore, US assessment of tibialis anterior muscle thickness appeared to be a promising index of muscle quantity, strength, and performance, correlating both with dynamometer and physical tests [30][31][32][33]. Other characteristics have been investigated as parameters for skeletal muscle evaluation, such as altered echogenicity, which traditionally correlates with lower muscle quality and reduced strength [34], perfusion, and also muscle elasticity [35].…”
Section: Introductionmentioning
confidence: 99%